2016
DOI: 10.1111/ane.12694
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease in Germany: prevalence and incidence based on health claims data

Abstract: BackgroundIn Germany, epidemiological information on Parkinson's disease (PD) is rare and outdated. Considering aging populations, current prevalences and incidence rates about this age‐related disease would be important for adequate public health planning.MethodsWe used newly available health claims data sets from the largest German health insurer dating 2004‐2007 and 2007‐2010 with an analysis population in the base years of 491 038 persons aged 50 and older. Quarter‐specific information about ICD‐10 diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
50
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 28 publications
(60 reference statements)
5
50
0
13
Order By: Relevance
“…In a study in Germany, one of the necessary criterion for defining PD using claim data was PD drug prescriptions. 36 Second, as our data are based on secondary data, there could be some misclassification of event timing. For example, there could be lags among PD onset, PD diagnosis, and PD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in Germany, one of the necessary criterion for defining PD using claim data was PD drug prescriptions. 36 Second, as our data are based on secondary data, there could be some misclassification of event timing. For example, there could be lags among PD onset, PD diagnosis, and PD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Males have been related to higher age-adjusted prevalence rates in many studies; in only a few studies did females have higher rates. 3,7,11,14,15,[17][18][19] Several other studies did not observe a statistically significant difference between gender and adjusted PD prevalence rates. 4,6,20 Results on the role of urban or rural living on prevalence of PD are controversial.…”
mentioning
confidence: 88%
“…[13][14][15] The existing body of research on PD epidemiology suggests that disease frequency peaks in the age-group 80-89 years old and then declines; 5,16,17 other studies have found the highest agespecific prevalence rates among the oldest groups studied. [13][14][15] The existing body of research on PD epidemiology suggests that disease frequency peaks in the age-group 80-89 years old and then declines; 5,16,17 other studies have found the highest agespecific prevalence rates among the oldest groups studied.…”
mentioning
confidence: 98%
See 2 more Smart Citations